Electromechanical properties of tetragonal Pb(In(1∕2)Nb(1∕2))O(3)−Pb(Mg(1∕3)Nb(2∕3))O(3)−PbTiO(3) ferroelectric crystals - Li, Fei (American Institute of Physics, 2010)
The ferroelectric, dielectric, elastic, piezoelectric, and electromechanical properties of tetragonal Pb(In(1∕2)Nb(1∕2))O(3)−Pb(Mg(1∕3)Nb(2∕3))O(3)−PbTiO(3) (PIN–PMN–PT) crystals were investigated. The single domain piezoelectric coefficients d(33), d(15), and d(31) were found to be 530, 2350, and −200 pC∕N, respectively, with electromechanical coupling factors k(33), k(15), and k(31) being on the order of 0.84, 0.85, and 0.58. The mechanical quality factor Q for longitudinal mode was found to be >700, with high coercive field (E(c)) being on the order of 10 kV∕cm. The temperature and dc bias electric-field characteristics of single domain tetragonal PIN–PMN–PT crystals were also investigated. In contrast to [001] oriented domain engineered rhombohedral crystals, tetragonal PIN–PMN–PT crystals exhibited broader temperature usage range and higher thermal∕electric field stability, with improved coercive field and mechanical quality factor.